The Impact of Social Assistance on the Social Welfare of PKH Beneficiary Families in Sentani District, Jayapura District - Mega Sari Wangloan; J. Ary Mollet; Hans Z. Kaiwai (LPPM STIE Krakatau, 2025)
Purpose: To assess the impact of social assistance and PKH on beneficiary welfare in Sentani District, identify key influencing factors, and evaluate government efforts to improve outcomes. Methodology/approach: The research applies a mixed-method approach, combining quantitative analysis (multiple linear regression, t-test, F-test) and qualitative techniques (interviews, data reduction, and thematic analysis). Respondents include 51 individuals from government agencies, community leaders, and PKH beneficiaries. Results/findings: Social assistance has a positive impact of 27.0% on welfare, while PKH contributes 21.6%. Jointly, both explain 48.6% of welfare improvement. Barriers include inaccurate targeting, budget limitations, infrastructure challenges, and socio-cultural constraints. Supporting factors include strong government policy, adequate funding, institutional cooperation, and active community participation. Conclusions: Both programs significantly improve welfare, but greater accuracy in targeting and timeliness of disbursement are needed to maximize impact. Limitations: The study is confined to one district with a small sample size, limiting broader applicability. Contribution: This research provides empirical evidence of the comparative impact of social assistance and PKH in Papua, offering policy recommendations to strengthen welfare programs in similar socio-economic contexts.